Urgency in The Existence of Publicness: Trans Jogja Bus Service as Public Transport in The Special Region of Yogyakarta - Septian, Esa; Fitrianto, Cipta Wahyu; Wulandari, Septi (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This research aims to see the extent of the existence of the Trans Jogja Bus as a mode of public transport in the Special Region of Yogyakarta. The publicness approach measures how public Trans Jogja Bus (BTJ) is in fulfilling the public interest and answers the urgency of overcoming congestion problems and providing services based on community needs. This research uses descriptive qualitative research, with data collection techniques of Interview, Observation, and Documentation. The informants who became data sources in this study include BTJ managers including PT AMI and Purasani pool, DIY Transportation Department, and BTJ service users. The results of this study found that the existence of BTJ in the public approach is as follows: 1) Service norms in BTJ's publicness degree are based on openness and socialization to the public, especially students. 2) Efforts to expand transport coverage on BTJ recipients, facilities, and route destinations. 3) The role of BTJ in reducing congestion is still not optimal because in operation it is often empty of passengers and congestion still occurs because private and online vehicles are the main choice for the community. 4) Efforts to build public trust in terms of organizational capability, leader quality, and passenger safety.